Penjatuhan Pidana Mati Pada Pelaku Tindak Pidana Mati Di Indonesia - syaiful bahri (Justicia Journal, 2012)
The problem in this research is how the implementation of the death penalty in Indonesia ?. This study aims to determine how the implementation of the death penalty in Indonesia. The approach used in the writing of this research is normative juridical law, the discussion is based on laws and regulations that apply to the problem of the death penalty in Indonesia, namely Law No. 2 / PNPS / 1964 on procedures for the implementation of capital punishment and the Law No. 3 1950 Clemency Law Number 22 Year 2002 regarding the petition for clemency in a way to examine the opinions of jurists literature is secondary data or literature. In analyzing the data used "Qualitative Methods" is a way of research that produces descriptive data analytical.Provided that the implementation of the death penalty in Indonesia is difficult, because the number of procedures that can be taken prior to the implementation of the execution through a Judicial Review (PK) where the demand for a judicial review is not limited to a certain period of time. (Article 264 Criminal Procedure Code), as well as filing for clemency to the President.